Innovative Enterprise Architectures for Deploying Product-Service Systems in SME - Silva, J.; Simões, J. (PRO-VE 2018 Collaborative Networks of Cognitive Systems, 2018)
This exploratory research appreciates the conceptual adequateness of servitization business models for an Advanced Manufacturing Technology (AMT) SME in the Ornamental Stones (OS) cluster. It is argued for the inquiry process generated from the developed enterprise architecture (EA) as a significant research contribution to conduct fieldwork. The EA (theoretical contribution) was tested by gathering qualitative data from semi-structured interviews, unstructured observations and documentation. A discussion arose from empirical findings concerning the EA usefulness/usability to diagnose both the sponsor’ state-of-the-art and needs (practitioner contribution). Primary stages of servitization found in the case might become advanced, if digital business platforms, Industry4.0 and collaborative networks (VBE/VO) are deployed. However, strong feelings of ownership in OS SME have constrained servitization progress and threatened cluster survival. Nevertheless, “mandatory” Building Information Modeling in Architecture, Engineering and Construction generates requirements for collaboration, promoting competitive advantage and enabling advanced servitization. Thus, innovative EA should anticipate/match future business requirements.